Entrepreneurship, Agglomeration and Technological Change - Ács, Zoltán J.; Varga, Attila (Small business economics, 2005)
A growing body of literature suggests that variations across countries, in entrepreneurial activity and the spatial structure of economies could potentially be the source of different efficiencies in knowledge spillovers, and ultimately in economic growth. We develop an empirical model that endogenizes both entrepreneurial activity and agglomeration effects on knowledge spillovers within a Romerian framework. The model is tested using the GEM cross-national data to measure the level of entrepreneurship in each particular economy. We find that after controlling for the stock of knowledge and research and development expenditures, both entrepreneurial activity and agglomeration have a positive and statistically significant effect on technological change in the European Union.